Synthesis of Biomaterial-Based Hydrogels Reinforced with Cellulose Nanocrystals for Biomedical Applications - Pavan Kumar Dara; Mahadevan Raghavankutty; Karthik Deekonda; Anil Kumar Vemu; Visnuvinayagam Sivam; Suseela Mathew; Anandan Rangasamy; Ravishankar Chandragiri Nagarajarao; Senthilkumar Subramanian (International Journal of Polymer Science)
Cellulose nanocrystals (CNC) were prepared by formic acid hydrolysis and TEMPO- (2,2,6,6-tetramethyl-piperidine-1-oxyl-) mediated oxidation. The prepared CNCs were reinforced into biopolymers chitosan (CHI), alginate (ALG), and gelatin (GEL) to obtain “CNC-ALG-GEL” and “CNC-CHI-GEL” hydrogels. The synthesized hydrogels were characterized for physicochemical, thermal, and structural characterization using Fourier transform infrared spectroscopy (FT-IR), scanning electron microscopy (SEM), thermal gravity analysis (TGA), and X-ray diffraction (XRD) analyses. Notably, the reinforcement of CNC has not altered the molecular structure of a biopolymer as revealed by FT-IR analysis. The hydrogels reinforced with CNC have shown better thermal stability and miscibility as revealed by thermal gravity analysis. The physicochemical, thermal, and structural characterization revealed the chemical interaction and electrostatic attraction between the CNC and biopolymers. The biocompatibility was investigated by evaluating the viability of the L929 fibroblast cell, which represents good biocompatibility and nontoxic nature. These hydrogels could be implemented in therapeutic biomedical research and regenerative medicinal applications.